Aplikasi Rumah Laundry Berbasis Web Menggunakan Rapid Application Development - Herjunadi Wicaksono (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2022)
Laundry house is a business engaged in laundry services. Every day the laundry house can receive about 20 to 25 laundry per day. Most data management processes are still carried out manually, starting from customer data registration, recording transaction data, and even for making reports still written in the general ledger. This causes various problems such as, the difficulty of finding customer data, making complicated reports because they have to recap transaction data that takes a long time and is not efficient. The creation of a Web-Based Laundry Application at a Laundry House using Rapid Application Development (RAD) models that aims to make it easier for employees to serve costamers, with this Web-Based Laundry Application, employees can more quickly handle transactions quickly and accurately so that transaction calculations can be done quickly based on the service chosen by the customer. With the Web-Based Laundry Application, it is also easier for laundry business actors to monitor their daily income in real time, see the busiest time in the field and make accurate reports automatically.